2001
DOI: 10.1046/j.1365-294x.2001.01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of endophytic fungi of single Norway spruce needles and their role as pioneer decomposers

Abstract: The diversity of endophytic fungi within single symptomless Norway spruce needles is described and their possible role as pioneer decomposers after needle detachment is investigated. The majority (90%) of all 182 isolates from green intact needles were identified as Lophodermium piceae. Up to 34 isolates were obtained from single needles. Generally, all isolates within single needles had distinct randomly amplified microsatellite (RAMS) patterns. Single trees may thus contain a higher number of L. piceae indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 27 publications
5
90
2
4
Order By: Relevance
“…Previous studies suggested a lower overlap between fungi of leaves and litter and faster species turnover during early decomposition (Müller et al 2001;Osono 2006;Voríšková and Baldrian 2013;Szink et al 2016). These studies were mostly locally restricted, and agree largely with the conditions we observed for single plots.…”
Section: Overlap Of Phyllosphere Mycobiomes and Fungal Litter Communisupporting
confidence: 91%
“…Previous studies suggested a lower overlap between fungi of leaves and litter and faster species turnover during early decomposition (Müller et al 2001;Osono 2006;Voríšková and Baldrian 2013;Szink et al 2016). These studies were mostly locally restricted, and agree largely with the conditions we observed for single plots.…”
Section: Overlap Of Phyllosphere Mycobiomes and Fungal Litter Communisupporting
confidence: 91%
“…Phyllosphere fungi might contain primary saprotrophs (Hudson 1968) that readily utilize carbohydrates and generate a more favourable environment for the colonization of fungi capable of decomposing more recalcitrant substances. Müller et al (2001) found that endophytic fungi act as pioneer decomposers in surface-sterilized spruce needles when incubated for 5 months on sterile and non-sterile soils. Furthermore, endophytic fungi were an active part of the needle-decay community during the entire two-year decomposition study (Korkama-Rajala et al 2007).…”
Section: Fungal Communitymentioning
confidence: 97%
“…The genetic diversity reflected within each site could be attributed to the lifestyle of endophytic Botryosphaeriaceae. As Class III endophytes they inhabit small localised pockets of their host (Müller et al 2001;Rodriguez et al 2009) and multiple genotypes can be found within a single host (Müller et al 2001). Therefore amongst numerous hosts the overall genetic diversity would be expected to be high.…”
Section: Mode Of Reproductionmentioning
confidence: 99%